Implementation with farsighted agents - Ville Korpela; Michele Lombardi; Hannu Vartiainen (Aboa Centre for Economics (ACE), 2021)
Agents are farsighted when they consider the ultimate consequences of their actions. We re-examine the classical questions of implementation theory under complete information in a setting with transfers, where farsighted coalitions are considered fundamental behavioral units, and the equilibrium outcomes of their interactions are predicted via the stability notion of the largest consistent set. The designer's exercise consists of designing a rights structure that formalizes the idea of power distribution in society. The designer's challenge lies in forming a rights structure in which the equilibrium behavior of agents always coincides with the recommendation given by a social choice rule. We show that (Maskin) monotonicity fully identifies the class of implementable single-valued social choice rules. Even though, monotonicity is not necessary for implementation in general, we show that every monotonic social choice rule can be implemented. These findings imply that the class of implementable social choice rules in core equilibria is unaltered by farsighted reasoning.
Keywords: C72; C78; D47; D71; 330; Implementation; rights structures; largest consistent set; core; (Maskin) monotonicity